1975
DOI: 10.1180/minmag.1975.040.309.11
|View full text |Cite
|
Sign up to set email alerts
|

A Mössbauer study of thermal decomposition of biotites

Abstract: SUMMARY. The effect of heat treatment in air at temperatures from 200 ~ to iooo ~ of two Cornish biotites has been studied using the M6ssbauer effect in 57Fe. One of the micas was also studied after heating in vacuo.Progressive changes in the M6ssbauer spectra of the materials after heat treatment can be correlated with the following processes: Oxidation of Fe 2+ ions in isolated octahedral sites to give Fe 3+ in the co-ordination Fe3+(OsOH); oxidation of Fe ~+ ions in adjacent a-octahedral (cis OH-) sites to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 14 publications
4
31
0
Order By: Relevance
“…The latter temperature of complete oxidation, for a 5 h exposure, is significantly lower than that found in natural biotite samples heated for comparable durations (e.g. Farmer et al, 1971;Gtittler et al, 1989;Hellner and Euler, 1957;Hogg and Meads, 1975;Ivanitskiy et aL, 1975;Rancourt et al, 1993a;Robert, 1971;Sanz et al, 1983;Vedder and Wilkins, 1969). This difference can be attributed to two special characteristics of our sample: its large Fe content and its small particle size.…”
Section: Crystal Chemical Nature Of the Oxidationmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter temperature of complete oxidation, for a 5 h exposure, is significantly lower than that found in natural biotite samples heated for comparable durations (e.g. Farmer et al, 1971;Gtittler et al, 1989;Hellner and Euler, 1957;Hogg and Meads, 1975;Ivanitskiy et aL, 1975;Rancourt et al, 1993a;Robert, 1971;Sanz et al, 1983;Vedder and Wilkins, 1969). This difference can be attributed to two special characteristics of our sample: its large Fe content and its small particle size.…”
Section: Crystal Chemical Nature Of the Oxidationmentioning
confidence: 99%
“…This is consistent with all of the Fe being oxidized by the oxybiotite reaction, without the vacancy reaction being required for further oxidation as would be the case in more Fe-rich samples. All authors who have studied thernaal decomposition of biotite in air or in vacuum (Farmer et al, 1971;Ferrow, 1987;Gfittler et al, 1989;Hogg and Meads, 1975;Ivanitskiy et al, 1975;Rancourt et al, 1993a;Rimsaite, 1970;Robert, 1971;Sanz et al, 1983;Tricker et al, 1976;Vedder and Wilkins, 1969) have found the first Fe oxidation reaction to be the oxybiotite reaction. Farmer et al (197l) concluded that the vacancy reaction (reaction 2) only occurred at higher temperatures than the temperatures where the oxybiotite reaction acted and only in biotites that were sufficiently Fe rich.…”
Section: Sequence Of Oxidation Reactions and Minimization Of Free Energymentioning
confidence: 99%
See 2 more Smart Citations
“…The two processes may be separated by thermal oxidation of the iron succeeded by acid dissolution of the hydroxide interlayer (Ross and Kodama, 1974;Goodman and Bain, 1979). During dry thermal oxidation, the layer charge remains constant by the release of one hydrogen atom per oxidized Fe(II), as suggested in the oxidation of biotite (Vedder and Wilkins, 1969;Farmer et al, 1971;Veith and Jackson, 1974;Hogg and Meads, 1975;Tripathi et al, 1978;Bagin et al, 1980), chlorite (Makumbi and Herbillon, 1972;Goodman and Bain, 1979), and smectite Heller-Kallai, 1976a, 1976b). For chlorite, the mechanism of this hydrogen release is obscure, as is the reversibility of the oxidation step.…”
Section: Introductionmentioning
confidence: 99%